Detection of Aortic Arch Calcification in Apolipoprotein E‐Null Mice Using Carbon Nanotube–Based Micro‐CT System. Issue 1 (13th February 2013) - Wait, John M. S.; Tomita, Hirofumi; Burk, Laurel M.; Lu, Jianping; Zhou, Otto Z.; Maeda, Nobuyo; Lee, Yueh Z.
Abstract : Background: We performed in vivo micro‐computed tomography (micro‐CT) imaging using a novel carbon nanotube (CNT)–based x‐ray source to detect calcification in the aortic arch of apolipoprotein E (apoE)–null mice. Methods and Results: We measured calcification volume of aortic arch plaques using CNT‐based micro‐CT in 16‐ to 18‐month‐old males on 129S6/SvEvTac and C57BL/6J genetic backgrounds (129‐apoE KO and B6‐apoE KO). Cardiac and respiratory gated images were acquired in each mouse under anesthesia. Images obtained using a CNT micro‐CT had less motion blur and better spatial resolution for aortic calcification than those using conventional micro‐CT, evaluated by edge sharpness (slope of the normalized attenuation units, 1.6±0.3 versus 0.8±0.2) and contrast‐to‐noise ratio of the calcifications (118±34 versus 10±2); both P <0.05, n=6. Calcification volume in the arch inner curvature was 4 times bigger in the 129‐apoE KO than in the B6‐apoE KO mice (0.90±0.18 versus 0.22±0.10 mm 3, P <0.01, n=7 and 5, respectively), whereas plaque areas in the inner curvature measured in dissected aorta were only twice as great in the 129‐apoE KO than in the B6‐apoE KO mice (6.1±0.6 versus 3.7±0.4 mm 2, P <0.05). Consistent with this, histological calcification area in the plaques was significantly higher in the 129‐apoE KO than in the B6‐apoE KO mice (16.9±2.0 versus 9.6±0.8%, P <0.05, 3 animals for each). Conclusions: A novel CNT‐based micro‐CT is a useful tool to evaluate vascular calcifications in living mice. Quantification from acquired images suggests higher susceptibility to calcification of the aortic arch plaques in 129‐apoE KO than in B6‐apoE KO mice.